Identification of Quantitative Resistance to Puccinia striiformis and Puccina triticinia in the Soft Red Winter Wheat Cultivar 'Jamestown'. Issue 6 (7th September 2017) - Carpenter, Neal R.; Griffey, Carl A.; Malla, Subas; Barnett, Marla; Marshall, David; Fountain, Myron O.; Murphy, J. Paul; Milus, Eugene; Johnson, Jerry; Buck, James; Chao, Shiaoman; Brown‐Guedira, Gina L.; et al.
Abstract : Disease resistance is critical in soft red winter wheat ( Triticum aestivum L.) cultivars. Leaf rust caused by Puccinia triticina Eriks and stripe rust caused by Puccinia striiformis Westend. f. sp. tritici Eriks. are destructive pathogens of wheat. Phenotypic data were collected at diverse locations for resistance to leaf rust (North Carolina, Texas, and Virginia) and stripe rust (Arkansas, North Carolina, Georgia, Texas, and Virginia) in a Pioneer '25R47' /'Jamestown' (P47/JT) population composed of 186 F5:9 recombinant inbred lines (RILs). The P47/JT RILs were genotyped with a public 90K iSelect single‐nucleotide polymorphism array. Analysis of the P47/JT population identified two quantitative trait loci (QTL) for leaf rust resistance on chromosome 5B and two QTL for stripe rust resistance on chromosomes 3B and 6A. These QTL were associated with both infection type and disease severity. Phenotypic variation (%) explained by the putative leaf rust resistance QTL of Jamestown on 5B was as high as 22.1%. Variation explained by the putative stripe rust resistance QTL of Jamestown on 3B and 6A was as high as 11.1 and 14.3%, respectively. Introgression and pyramiding of these QTL with other genes conferring resistance to leaf and stripe rusts via marker‐assisted selection will facilitate development of soft red winter wheat cultivars having more durable resistance.